Hubungan Berat Badan Lahir dengan Status Nutrisi Pada Balita di Wilayah Kerja Puskesmas Undaan Kabupaten Kudus - Muhammad Dimas Al-Abab Sutrisno; Umi Faridah; Sukarmin Sukarmin (Universitas Pahlawan Tuanku Tambusai, 2025)
This research is motivated by the high prevalence of problems with the nutritional status of children under five in Indonesia, such as stunting, wasting and overweight, which have a significant impact on the quality of human resources in the future. One of the main factors contributing to this problem is low birth weight (LBW), which reflects a lack of nutritional intake during pregnancy. LBW conditions can trigger various long-term health risks in toddlers, including growth disorders, stunting and malnutrition. The nutritional status of toddlers is assessed through various anthropometric indicators, such as body weight, height and body mass index (BMI), thus providing a comprehensive picture of the balance of nutritional intake and body needs. This research was carried out in the work area of the Undaan Community Health Center, Kudus Regency, involving a population of 83 toddlers. From this population, 68 toddlers were selected as samples based on predetermined inclusion criteria. Data collection was carried out through direct measurements of the toddler's weight and height and using a questionnaire that included information related to birth weight and nutritional patterns. Data analysis was carried out in stages, starting from univariate analysis to map data distribution, followed by bivariate analysis using the Spearman test to identify the relationship between birth weight and nutritional status of toddlers. The results of the study showed that there was a statistically insignificant relationship between birth weight and nutritional status of toddlers with a value of p = 0.442 (p > 0.05). However, birth weight remains one of the factors that can influence a child's nutritional development during the growth period. Therefore, it is necessary to educate mothers regarding the importance of fulfilling nutrition during pregnancy and monitoring the growth of toddlers regularly. It is hoped that the Community Health Center can improve its nutrition education program to optimize the growth and development of toddlers and prevent malnutrition problems.